Dysbiosis of Gut Microbiota and Lipidomics of Content Induced by Dietary Methionine Restriction in Rice Field Eel (Monopterus albus) - Hu, Yajun; Cai, Minglang; Chu, Wuying; Hu, Yi (Frontiers in Microbiology, 2022)
An eight-week feeding trial was conducted with six isonitrogenous and isoenergetic experimental feeds were supplemented different levels of methionine (0, 2 g/kg, 4 g/kg, 6 g/kg, 8 g/kg, or 10 g/kg) in basic feed on rice field eel Monopterus albus. This study was based our previous studies that dietary methionine restriction (M0, 0 g/kg) inhibited hepatic fatty acid metabolism and intestinal fatty acid transportation, while supplemented suitable level of methionine (M8, 8g/kg) improved hepatic lipid metabolism and intestinal fatty acid transportation, hence, M0 (0 g/kg) and M8 (8 g/kg) were chose to know how methionine regulates gut microbiota and lipidomics of Monopterus albus. Compared with M0, gut bacterial Sobs, Shannon, ACE and Chao1 in M8 were remarkably increased (P < 0.05), Fusobacteria, Firmicutes and Proteobacteria were the main community of phylum, Cetobacterium, Plesiomonas and Bacillus were the main community of genus among M0 and M8. Compared with M0, the proportion of Fusobacteria of phylum decreased in M8, Cetobacterium and Lactococcus of genus decreased in M8; while proportion of Firmicutes, Proteobacteria and Chioroflexi of phylum increased in M8, and Clostridium and Streptococcus of genus increased in M8. Many edges were presented in circus and networks showed the interspecies interactions among different OTUs. In addition, various OTUs in same phylum were clustered within one module. Cooperative interactions were predominant in the two networks, while competitive interactions predominated in the submodules. Gut microbiota mainly played role in nutrition (lipid, amino acid and carbohydrate) transport and metabolism among M0 and M8. The PLS-DA score indicated that there has significant difference of main component of lipidomics between M0 and M8. Such as TG(26:0/16:0/17:0), TG(28:0/16:0/16:0), TG(26:0/16:0/16:0), TG(30:0/16:0/16:0), etc. of gut content in M8 were remarkably decreased (P < 0.001). Clostridium of genus has positive correlation with TG(18:1/18:1/22:5), TG(16:0/17:0/18:1), TG(18:0/18:1/20:3), etc., while has negative correlation with TG(18:0/17:0/20:0), TG(16:0/17:0/24:0), TG(16:0/16:0/24:0), etc. The lipidomics predicted the KEGG pathway main included lipid and glycan biothesis and metabolism, main system included digestive, sensory and immune system. In conclusion, methionine restriction disturbed the balance of microbial community and induced microbial dysfunctions, while supplemented methionine improved the gut microbiota homeostasis and lipid metabolism.